Lignocellulosic acid hydrolysis inhibitor impact on 5-hydroxymethylfurfural biotransformation into 2, 5-furandicarboxylic acid using immobilised Burkholderia cells. Issue 4 (4th July 2022) - Tsai, Jia-Yin; Lu, Ping-Yan; Yang, Chu-Fang
Abstract: Acid hydrolysis extensively applies as an economical pre-treatment to obtain monosaccharides from recalcitrant lignocellulosic residues. However, inhibitors are inevitably formed and reduce the downstream biofuel yield. Our bacterial isolate Burkholderia cepacia H-2 was capable of biotransforming 5-hydroxymethylfurfural (5-HMF), a common inhibitor, into valuable 2, 5-furan-dicarboxylic acid (FDCA). This isolate also has potential use for detoxifying other inhibitors derived from lignocellulosic acid hydrolysis. To integrate this strain into further lignocellulosic biofuel production processes, strain B. cepacia H-2 was immobilised to biotransform 5-HMF into FDCA and detoxify various inhibitors. Strain B. cepacia H-2 could biotransform 5-HMF into FDCA in the presence of inhibitors derived from lignocellulosic acid hydrolysis and detoxified formic acid, furfural and levulinic acid. The negative effect of approximately 500 mg L −1 inhibitor on 5-HMF biotransformation was as follows (from strongest to weakest): furfural > acetic acid > phenol > formic acid > levulinic acid. Graphical Abstract: UF0001